2021
DOI: 10.3389/fnut.2021.668514
|View full text |Cite
|
Sign up to set email alerts
|

The Consumption of Energy Drinks Induces Blood-Brain Barrier Dysfunction in Wild-Type Mice

Abstract: Energy drinks containing significant quantities of caffeine and sugar are increasingly consumed, particularly by adolescents and young adults. Chronic ingestion of energy drinks may potentially regulate vascular risk factors. This study investigated the effects of chronic ingestion of energy drinks on blood-brain barrier (BBB) integrity and neuroinflammation. Male C57BL/6J mice were maintained on water (control), MotherTM (ED), sugar-free MotherTM (sfED), or Coca ColaTM soft drink (SD) for 13 weeks. The BBB in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…Systolic pressure in the sugar-free ED-treated mice was significantly lower than in the control group. Comparing the diastolic and mean arterial pressures to the control group, similar substantial reductions were seen [126].…”
Section: Long-term Studies On Animalssupporting
confidence: 53%
“…Systolic pressure in the sugar-free ED-treated mice was significantly lower than in the control group. Comparing the diastolic and mean arterial pressures to the control group, similar substantial reductions were seen [126].…”
Section: Long-term Studies On Animalssupporting
confidence: 53%
“…In this context, it has been demonstrated that caffeine does not alter the blood–brain barrier [ 14 ], thus, leading to no alteration in brain parenchyma physiology and homeostasis. However, on the other hand, energy drinks are able to induce blood–brain barrier dysfunction, as recently demonstrated [ 15 ], and this side effect could explain the previously observed brain oxidative stress in rats under an energy drink condition [ 16 ]. Now, it is increasingly evident that non-toxic doses of caffeine mostly act on biological tissues by the antagonism of adenosine receptors, as first stated by Fredholm [ 17 ].…”
Section: Introductionmentioning
confidence: 94%
“…">IntroductionEnergy drinks are carbonated beverages that are devoid of alcohol and are specifically formulated to provide the customer with a boost of energy. The global use of energy drinks has witnessed a significant rise since its debut in the markets in the 1960s [1]. Energy drinks are composed of several components, including caffeine, taurine, guarana, glucuronolactone, vitamins, and carbs, alongside water.…”
mentioning
confidence: 99%